Estrous cycle impacts microRNA content in extracellular vesicles that modulate bovine cumulus cell transcripts during in vitro maturation. Issue 2 (2nd September 2019) - de Ávila, Ana Clara Faquineli Cavalcante Mendes; Bridi, Alessandra; Andrade, Gabriella Mamede; del Collado, Maite; Sangalli, Juliano Rodrigues; Nociti, Ricardo Perecin; da Silva Junior, Wilson Araújo; Bastien, Alexandre; Robert, Claude; Meirelles, Flávio Vieira; Perecin, Felipe; da Silveira, Juliano Coelho
Abstract: Extracellular vesicles (EVs) are nanoparticles secreted by ovarian follicle cells. Extracellular vesicles are an important form of intercellular communication, since they carry bioactive contents, such as microRNAs (miRNAs), mRNAs, and proteins. MicroRNAs are small noncoding RNA capable of modulating mRNA translation. Thus, EVs can play a role in follicle and oocyte development. However, it is not clear if EV contents vary with the estrous cycle stage. The aim of this study was to investigate the bovine miRNA content in EVs obtained from follicles at different estrous cycle stages, which are associated with different progesterone (P4) levels in the follicular fluid (FF). We collected FF from 3 to 6 mm follicles and evaluated the miRNA profile of the EVs and their effects on cumulus-oocyte complexes during in vitro maturation. We observed that EVs from low P4 group have a higher abundance of miRNAs predicted to modulate pathways, such as MAPK, RNA transport, Hippo, Cell cycle, FoxO, oocyte meiosis, and TGF-beta. Additionally, EVs were taken up by cumulus cells and, thus, affected the RNA global profile 9 h after EV supplementation. Cumulus cells supplemented with EVs from low P4 presented upregulated genes that could modulate biological processes, such as oocyte development, immune responses, and Notch signaling compared with genes of cumulus cells in the EV free media or with EVs from high P4 follicles. In conclusion, our results demonstrate that EV miRNA contents are distinct in follicles exposed to different estrous cycle stage. Supplementation with EVs impacts gene expression and biological processes in cumulus cells. Abstract : MicroRNA contents of small EVs obtained from bovine follicular fluid are modified depending on the estrous cycle stage and can modulate the RNA profile of cumulus cells during in vitro oocyte maturation.